Plasma membrane targeted photodynamic O2 economizer for hypoxic tumor therapy. (June 2021) - Fan, Gui-Ling; Deng, Fu-An; Zhou, Xiang; Liu, Ling-Shan; Huang, Jia-Qi; Zhang, Da-Wei; Sun, Yun-Xia; Chen, A-Li; Cheng, Hong; Li, Shi-Ying
Abstract: The development of photodynamic therapy (PDT) is severely limited by short half-life of singlet oxygen ( 1 O2 ) and the hypoxic microenvironment. In this work, a plasma membrane targeted photodynamic O2 economizer (designated as P-POE) is developed to improve the subcellular delivery of photosensitizers and alleviate the tumor hypoxia for enhanced PDT effect. After self-assembly into nanomicelles, P-POE has a relatively high stability and a favorable photochemical performance, which are conducive to boosting the 1 O2 production. Besides, the plasma membrane anchoring of P-POE contributes to enhancing the preferential retention and cellular accumulation of photosensitizers on tumor tissues and cells. More importantly, P-POE-induced mitochondrial respiratory depression is demonstrated to reduce the O2 consumption of tumor cells to relieve the hypoxia. Consequently, P-POE still exhibits a robust PDT effect against hypoxic tumors, which greatly inhibits the proliferation of breast cancer with low adverse reactions. This innovative combination of subcellular targeting and hypoxic alleviation would advance the development of individualized drug delivery systems for photodynamic therapy against hypoxic tumors.